Psychometric properties of the ethical conflict in nursing questionnaire critical care version among Chinese nurses: a cross-sectional study - Liu, Yuanfei (BMC Nurs, 2021)
BACKGROUND: Ethical conflicts are common in the critical care setting, and have compromised job satisfaction and nursing care quality. Using reliable and valid instruments to measure the ethical conflict is essential. This study aimed to translate the Ethical Conflict in Nursing Questionnaire — Critical Care Version into Chinese and determine the reliability and validity in the population of Chinese nurses. METHODS: Researchers obtained permission and followed the translation-backward method to develop the Chinese version of the Ethical Conflict in Nursing Questionnaire — Critical Care Version (ECNQ-CCV-C). Relevant psychometric properties were selected according to the Consensus-based standards for the selection of health status measurement instruments checklist. Critical care nurses were recruited from two tertiary public hospitals in Hangzhou, Zhejiang Province, and Kunming, Yunnan Province. Of the 264 nurses we approached, 248 gave their consent and completed the study. RESULTS: The ECNQ-CCV-C achieved Cronbach’s alphas 0.902 and McDonald’s omega coefficient 0.903. The test-retest reliability was satisfactory within a 2-week interval (intraclass correlation coefficient = 0.757). A unidimensional structure of the ECNQ-CCV-C was determined. Confirmatory factor analysis supported acceptable structure validity. Concurrent validity was confirmed by a moderate relation with a measure for hospital ethical climate (r = − 0.33, p < 0.01). The model structure was invariant across different gender groups, with no floor/ceiling effect. CONCLUSIONS: The ECNQ-CCV-C demonstrated acceptable reliability and validity among Chinese nurses and had great clinical utility in critical care nursing. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12912-021-00651-x.